346 Pre-clinical characterization of AZD0240, a CRISPR-engineered autologous TCR-T cell product targeting KRAS-G12D/HLA-A11:01 that is multi-armored to increase epitope sensitivity - Kok Lianne; Eshuis Sander; Kong Xiangjun; Ma, Jennifer; Mojadidi Michelle; Hall, Elizabeth; Grace Sun Ka Hei; Kroon, Paula; Tubb, Vanessa; Schumacher, Ton; Perez, Arianne; Linnemann Carsten; et al. (Journal for immunotherapy of cancer, 2025)
BackgroundKRAS is one of the most mutated genes in human cancer, with the G12D mutation having the highest frequency, occurring in 28% and 12% of pancreatic cancer (PDAC) and colorectal cancer (CRC), respectively. KRAS G12D-containing peptides are presented by the common HLA allele HLA-A*11:01, making this cancer neoantigen a highly attractive target for the development of adoptive TCR-T cell therapy. However, the levels of cancer neoantigen presentation are typically low and combined with the immunosuppressive tumor microenvironment this compromises the activation and reactivity of TCR-engineered T cells, posing a major hurdle for these cells to eradicate tumor lesions.MethodsTo establish a TCR-T cell therapy intended for the treatment of solid cancers, including PDAC and CRC, we developed AZD0240, a CRISPR-engineered autologous TCR-T cell product targeting KRAS-G12D/HLA-A*11:01. To improve the reactivity of AZD0240 to the KRAS-G12D neoantigen, we developed a novel multi-armoring strategy, involving the combined disruption of a key negative regulator of T cell function and the introduction of a positive enhancement of TCR signaling.ResultsEmploying this multi-armoring strategy, we observed enhanced cytokine production in response to low levels of exogenously loaded KRAS-G12D peptide, as well as to HLA-A*11:01+ tumor cells that express the KRAS-G12D mutation. Moreover, assessment of the in vitro and in vivo proliferative and cytotoxic capacity revealed that the AZD0240 armoring strategy profoundly increased both the clonal expansion and the anti-tumor efficacy of TCR-engineered T cells. Notably, the armored AZD0240 T cells were unable to respond to the KRAS G12 wild-type epitope, and no signs of increased TCR cross- or allo-reactivity, or malignant transformation were detected, derisking the clinical use of this armoring strategy.ConclusionsTaken together, AZD0240 is a KRAS-G12D/HLA-A*11:01-targeted TCR-T cell therapy that employs a novel multi-armoring strategy and is currently in preparation for clinical testing, with encouraging signs of pre-clinical efficacy and safety.